Pengaruh Konflik Peran Ganda (Work Family Conflict), Ambiguitas Peran, dan Stres Kerja terhadap Kinerja Staf Karyawati (Studi pada Universitas Nahdlatul Ulama Surabaya) - Riyan, Riyan Sisiawan Putra; Aziza, Firda Nur; Khusnah, Hidayatul; Utami, Tri (JURNAL AKUNTANSI DAN MANAJEMEN, 2021)
This study deals with how the influence of dual role conflict, role ambiguity and job stress on the performance of female employees at Nahdlatul Ulama University Surabaya. The purpose of this study was to determine the effect of multiple role conflict, role ambiguity and job stress on employee performance. Respondents in this study were 82 employees of Naahdlatul Ulama University Surabaya. The data collection method used is using a questionnaire. This study uses dual role conflict as an independent variable, role ambiguity as an independent variable, job stress as an independent variable and employee staff performance as the dependent variable. The sampling technique used in this research is probability sampling method. The analysis used is the classical assumption test, validation test, reliability test, multiple linear regression analysis, hypothesis testing, coefficient of determination. This study shows that there is a significant effect of dual role conflict on the performance of female employees and, a significant effect of role ambiguity on the performance of female employees and, a significant effect of job stress on the performance of female employees.